2021
DOI: 10.3390/info12080300
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Three Methodological Approaches in the Use of Gamification in Vocational Training

Abstract: A reduced interest and low motivation in learning amongst vocational students has become a challenge with many traditional strategies not capable of providing a solution to motivation and encouraging participation in learning. The use of elements of games in non-recreational environments (gamification) may be a possible solution, since research indicates an improvement in user experience and engagement, with possibilities of improved motivation and behavioral results. However not all studies obtain positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…From the reviewed literature, the author identified five game technologies used, as shown in Table 5 . Three studies (Garcia-Iruela et al, ( 2021 ); Jayalath et al, ( 2022 ); Tongpaeng et al, ( 2019 )) employed the Moodle application, which can support MOOC as their learning management system to deliver online courses, while two studies (Kladchuen and Srisomphan, ( 2021 ); Kummanee et al, ( 2020 )) designed a problem-based learning model which consisted of a digital learning platform in the early design stage. Four studies used an enriched experience in the real world and virtual settings in their educational delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the reviewed literature, the author identified five game technologies used, as shown in Table 5 . Three studies (Garcia-Iruela et al, ( 2021 ); Jayalath et al, ( 2022 ); Tongpaeng et al, ( 2019 )) employed the Moodle application, which can support MOOC as their learning management system to deliver online courses, while two studies (Kladchuen and Srisomphan, ( 2021 ); Kummanee et al, ( 2020 )) designed a problem-based learning model which consisted of a digital learning platform in the early design stage. Four studies used an enriched experience in the real world and virtual settings in their educational delivery.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few terms are commonly used: points, feedback, levels, leader boards, challenges, badges, avatars, competition, and cooperation. From the author’s search of the literature, four studies (Garcia-Iruela et al, 2021 ; Jayalath et al, 2022 ; Kladchuen & Srisomphan, 2021 ; Kummanee et al, 2020 ) included several game elements such as points, badges, levels, leader boards, blocked content, time limit, trophies, virtual goods and spaces feedback and progress bar in the LMS/MOOC to motivate students, increase participation, embark high interest in learning and improve satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A gamification design contains the most common elements in three methodological approaches (teacher-centered, studentcentered and mixed) 10. The didactic-pedagogical strategies are aesthetically configured as gamification, since they conjecture the educational system as an emerging phenomenon, product the popularity of games, digital literacy in cyberculture, and their ability to motivate actions, solve problems, improve learning in various fields of knowledge 23, 36-56. By highlighting these peculiarities, it is observed that, in an authorial proposal of gamification of virtual education environments, the interest and involvement of the participants in assuming challenges, solving problems and carrying out activities increases, resulting in a greater probability of resignification.…”
Section: Methodological Strategiesmentioning
confidence: 99%
“…The use of game elements in non-recreational settings (gamification) may be a possible solution, as research indicates an improvement in user experience and engagement, with the potential to improve motivation and behavioral outcomes. However, not all studies obtain positive results, the success of gamification is influenced by the design, the sample, and the context 10 .…”
Section: Motivation and Gamificationmentioning
confidence: 99%
“…The inclusion of gamification, accompanied by badges, levels, leader boards, rewards, etc. generates greater motivation and commitment among students to actively participate ( Garcia-Iruela et al, 2021 ), and there is evidence of a great deal of best practice in this regard.…”
Section: Theoretical Frameworkmentioning
confidence: 99%